2017
DOI: 10.37358/rc.17.7.5730
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sleeve Gastrectomy and Conservatory Treatment Effect on Biochemical and Hormonal Profile of Obese Type 2 Diabetes Subjects: CREDOR Randomized Controlled Study Results

Abstract: Metabolic surgery is the most efficacious method for the treatment of morbid obesity and was recently included among the antidiabetes treatments recommended in obese type 2 diabetes (T2D) patients. The aim of this study was to compare in a randomized controlled trial the effect of sleeve gastrectomy (SG) to that of intensive lifestyle intervention plus pharmacologic treatment on some markers of insulin resistance and beta cell function as well as some appetite controlling hormones in a group of male obese T2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…No participant had any diagnosed systemic immune disorders and was known to be taking any form of vitamin supplementation neither at the time of recruitment nor after inclusion in this study. Detailed information regarding the procedures of this study was previously reported [16]. Briefly, 17 patients from the DTG and 19 from the LSG were evaluated after 6 months of follow up.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…No participant had any diagnosed systemic immune disorders and was known to be taking any form of vitamin supplementation neither at the time of recruitment nor after inclusion in this study. Detailed information regarding the procedures of this study was previously reported [16]. Briefly, 17 patients from the DTG and 19 from the LSG were evaluated after 6 months of follow up.…”
Section: Patientsmentioning
confidence: 99%
“…All subjects consulted a nutritionist before and during the study for dietary advice and instructions on preparation of their diets to assure good adherence to the study. Detailed presentation of the diet intervention was previously described [16]. In brief, individualized calorie count was based on the estimated Resting Metabolic Rate (RMR) from which a 500 kcal daily restriction was subtracted.…”
Section: Patientsmentioning
confidence: 99%
“…Starting from the measured value for resting metabolic rate (RMR) and taking into account the "nutritional pattern" or identified dietary habits, a personalized diet was established for each patient from the conservative treatment group [46]. Specifically, the daily caloric requirement was calculated based on the formula [RMR * 1.3 (sedentary lifestyle) + (10% * RMR) (for the thermal effect of food) −500], thus inducing a 500 kcal daily restriction.…”
Section: Methodsmentioning
confidence: 99%
“…Starting from the measured value for resting metabolic rate (RMR) and taking into account the "nutritional pattern" or identified dietary habits, a personalized diet was established for each patient from the conservative treatment group [13]. Specifically, the daily caloric requirement was calculated based on the formula [RMR*1.3 (sedentary lifestyle) + (10% * RMR) (for the thermal effect of food) -500], thus inducing a 500-kcal daily restriction.…”
Section: Methodsmentioning
confidence: 99%